Baseline Hemodynamics Including Aortic and Pulmonary Blood Flow in a Chronic Bovine Model - Angel Moctezuma-Ramirez; Abdelmotagaly Elgalad; Kelly Handy; Gil Costas; O. H. Frazier (Surgeries, 2022)
The use of large animal models in the preclinical setting has expanded and become increasingly valuable for evaluating the safety and efficacy of new therapies and devices. Here, we report normal hemodynamic values, including aortic and pulmonary blood flow, in a bovine model at rest and during exercise after a control procedure. We performed a left lateral thoracotomy and implanted fluid-filled pressure lines (aortic pressure, right atrial pressure, left atrial pressure, pulmonary artery pressure) and left (systemic) and right (pulmonary) flow probe lines. Throughout the postoperative period, the calf’s physiologic pressures, vital signs, aortic and pulmonary blood flow, and pulmonary and systemic vascular resistance were recorded hourly at rest and during treadmill exercise evaluations. When pressures and flow rates at baseline and during treadmill trials were compared, we observed a physiologic response to exercise similar to that seen in humans, with a sympathetic discharge that increased systolic blood pressure. However, the rise in mean arterial pressure was much lower due to an overall decrease in vascular resistance, which increased blood flow. This study provides investigators, device engineers, and manufacturers with normal bovine cardiovascular physiology data that can be used for technical consideration during device development for preclinical trials.